Determinan risiko sistemik perbankan Indonesia: Aplikasi metode marginal expected shortfall - Mutiara Hikmah; Buddi Wibowo (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
The purpose of this study is to measure systemic risk with a method that is able to calculate predictions of bank capital losses when the market is in a crisis, namely Marginal Expected Shortfall (MES) and empirically test the factors that influence it. Systemic risk arises when banks experiencing capital losses and transmit the problem to other banks and to other financial companies so that the financial system collapses. This MES model has advantages over other systemic risk measurement models because it is calculated with data available in the market, namely stock prices and volatility so that we can measure each bank’s impact to banking systemic risks. This study shows that control variable such as Non-Performing Loans (NPL) influence systemic risk but other variables such as CAR, and bank profitability (ROA) do not have significant effect on systemic risk.